Human resource management influences on commitment - Stecca, Jaime Peixoto; Albuquerque, Lindolfo Galvão de; Von Ende, Marta (Revista de Administração da UFSM, 2017)
The study of organizational commitment and their antecedents and consequences, has taken an important place in the research agenda. It is appropriate in this agenda include cooperative societies, due to its importance in the generation and distribution of wealth. The objective of this study was to investigate the relationship between the strategies of human resource management adopted in credit cooperatives and the organizational commitment of their employees. To achieve this, an investigation was conducted with employees of credit cooperatives in the states of Rio Grande do Sul and Santa Catarina from three representative Brazilian credit cooperative systems - Sicredi, Sicoob and Unicred. It was studied employees´perception to the management strategies and their organizational commitment. A total of 388 people answered 33 questions about generic strategies of human resource management and 23 questions about organizational commitment, based on the model validated by Medeiros (2003). The data were analyzed using multivariate statistics, taking structural equation modeling (SEM) technique to test the causal relationship between the studied constructs. The results indicate that the adopted strategies of human resource management positively affect the organizational commitment of employees.